A Review of My Secret #EdTech Diary: Looking at Educational Technology Through a Wider Lens, A Book by Al Kingsley - Matthew David Botkin (Issues and Trends in Learning Technologies)
Technology has come to play an integral part in the educational process of students around the world. School administrators and teachers rely on technology to gather real-time data, provide meaningful feedback, and assess student learning. In 2020, school personnel across the globe needed to provide services to students despite limitations put in place by the COVID-19 pandemic. In My Secret #EdTech Diary: Looking at Educational Technology Through a Wider Lens, Al Kingsley analyzes post-pandemic lessons in the educational technology (EdTech) field from various viewpoints. Using his experience as the CEO of an educational software company and a member of a school board of governors, Kingsley describes lessons from the rapid development and use of educational technology during and after the COVID-19 pandemic.